2012
DOI: 10.5600/mmrr.002.03.a03
|View full text |Cite
|
Sign up to set email alerts
|

Volume of Home- and Community-Based Services and Time to Nursing-Home Placement

Abstract: Objective: The purpose of this study was to determine whether the volume of Home-and CommunityBased Services (HCBS) that target Activities of Daily Living disabilities, such as attendant care, homemaking services, and home-delivered meals, increases recipients' risk of transitioning from longterm care provided through HCBS to long-term care provided in a nursing home.Data Sources: Data are from the Indiana Medicaid enrollment, claims, and Insite databases. Insite is the software system that was developed for c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 26 publications
1
13
0
Order By: Relevance
“…Despite a substantial proportion entering RAC and using RAC on average 2.9 years [28], our finding suggests that increased use of HACC services can reduce the hazard of early admission to RAC, and consequently may reduce the length of stay in RAC. Several US-based regional studies reported that increased home-and community-based care use is associated with a reduced risk of transitioning to a nursing home [14][15][16]. A recent region-based Australian study demonstrated that one hour per week of HCP service use is associated with a 6% decrease in risk of time to entering RAC over the 18-month period [17].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite a substantial proportion entering RAC and using RAC on average 2.9 years [28], our finding suggests that increased use of HACC services can reduce the hazard of early admission to RAC, and consequently may reduce the length of stay in RAC. Several US-based regional studies reported that increased home-and community-based care use is associated with a reduced risk of transitioning to a nursing home [14][15][16]. A recent region-based Australian study demonstrated that one hour per week of HCP service use is associated with a 6% decrease in risk of time to entering RAC over the 18-month period [17].…”
Section: Discussionmentioning
confidence: 99%
“…Earlier studies have identified a number of risk factors to enter RAC, including older age, widowhood, living alone, low independence in activities in daily living (ADL), living in a flat or retirement village, falls, and cognitive impairment [11][12][13]. Besides the individuals' factors, greater volume of home-and community-based care use are associated with a reduced risk of subsequent nursing home admission in the USA [14][15][16]. A recent Australian study has demonstrated that each hour per week of HCP service use is associated with a 6% decreased risk of entering RAC [17].…”
Section: Introductionmentioning
confidence: 99%
“…Some studies focus on the health, functional status (need factors), and socioeconomic characteristics (predisposing and enabling factors) of older adults. In general, these studies show need and demand to be strongly and positively related to age, functional status (Gaugler, Duval, Anderson, & Kane, 2007; Chen & Sloan, 2015), demographic factors such as White race (Gaugler et al, 2007; Willink, Davis, & Schoen, 2016); female gender (Kinosian et al, 2000); living alone (Gaugler et al, 2007; Willink et al, 2016); poverty (Gaugler et al, 2007; Willink et al, 2016); chronic health conditions including diabetes, high blood pressure, stroke history, and psychiatric illness (Gaugler et al, 2007; Willink et al, 2016); physical disability (Fong, Mitchell, & Koh, 2015; Willink et al, 2016); and cognitive impairment (Sands et al, 2012; Willink et al, 2016).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Another category of studies has examined the effects of community-based care options such as adult day care, respite care, and/or other social support services (Fischer et al, 2003; McCann et al, 2005; Sands et al, 2012; Spillman, 2016; Thomas & Mor, 2013). Across studies, the strongest predictors of nursing home admission include activities of daily living (ADLs) dependency (three or more), cognitive impairment, and prior nursing home use (Gaugler et al, 2007).…”
Section: Literature Reviewmentioning
confidence: 99%
“…However, nearly 20 % of older adults who need ADL help report unmet need for assistance with their ADL . Unmet need for ADL assistance is associated with increased health care utilization including hospitalization , re‐hospitalization , and nursing home placement . Unmet need for ADL assistance is also associated with increased risk for death and, for many older adults, medical care expenditures increase significantly in the months before death .…”
Section: Introductionmentioning
confidence: 99%